Aliphatic polyester and use thereof
Patent Information
- Application Number
- KR1020260042802
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-10
- Filing Date
- 2026-03-10
- Publication Date
- 2026-09-17
Smart Images

Figure PAT00004 
Figure PAT00005
Abstract
Description
Technology Field
[0001] The present invention belongs to the field of polyester material technology, and specifically relates to aliphatic polyesters and their applications. Background Technology
[0002] Food preservation films are thin plastic packaging products that not only extend the shelf life of food but also maintain freshness by retaining moisture. More importantly, when used on opened beverage, fruit, or food containers, they can improve hygiene and safety by blocking bacteria. Consequently, food preservation films are widely used in household, supermarket, and industrial food packaging sectors. However, conventional food preservation films primarily utilize materials such as polyethylene, biaxially oriented polyester (BOPET), biaxially oriented polypropylene (BOPP), and chlorinated polypropylene (CPP); these films are non-biodegradable and easily cause "white contamination" after disposal.
[0003] To address the issue of low biodegradability in conventional food preservation films, biodegradability has been improved by replacing existing film materials with biodegradable polyesters such as polybutylene adipate terephthalate (PBAT). However, due to the entanglement between molecular chains of the PBAT resin, the crystallization rate of the material is slow and the film adhesion becomes strong. Consequently, during the curtain coating manufacturing process, the film easily adheres to stainless steel rollers, leading to frequent film breakage and affecting processing stability. At the same time, the strong adhesion of the film material makes it difficult to unwrap the manufactured food preservation film during use, degrading the user experience. To reduce the adhesion of the PBAT resin and improve unwrapability, conventional technologies have commonly used a method of mixing lubricants, such as epoxidized soybean oil, into the PBAT to enhance the unwrapability of the PBAT food preservation film. However, due to the difference in polarity between the lubricant and the PBAT resin, migration and sedimentation are prone to occur during use, increasing the risk of food contact.
[0004] Therefore, developing biodegradable food preservation films that simultaneously possess excellent unravelability and a low risk of food contact is an urgent task to be addressed in this field. The problem to be solved
[0005] The present invention aims to provide an aliphatic polyester and its applications to overcome the disadvantages of existing technologies. The aliphatic polyester is used to manufacture packaging films, particularly food-grade packaging films, thereby solving the problem that existing packaging films cannot simultaneously possess excellent unravelability and food contact safety, and exhibits excellent biodegradability to meet household composting requirements. means of solving the problem
[0006] To achieve the above objective, the present invention adopts the following technical solution.
[0007] In a first aspect, the present invention provides an aliphatic polyester, said aliphatic polyester comprising a binary acid residue and a diol residue: said binary acid residue comprises 65 to 90 mol% of a succinic acid residue based on 100 mol% of the total molar percentage of a1) and a2); said diol residue comprises 10 to 35 mol% of a sebacic acid residue based on 100 mol% of the total molar percentage of a1) and a2); said diol residue is selected from at least equimolar amounts of 1,4-butanediol residue with the binary acid residue; said aliphatic polyester comprises an oligomer having a number average molecular weight < 1000 as measured by GPC, and the mass percentage of the oligomer having a number average molecular weight < 1000 as measured by GPC in said aliphatic polyester is 0.08 to 3.5 wt%.
[0008] In the present invention, succinic acid and / or succinic acid derivatives are introduced into the polyester molecular chain through a polymerization reaction to form succinic acid residues; sebacic acid and / or sebacic acid derivatives are introduced into the polyester molecular chain through a polymerization reaction to form sebacic acid residues; and polybutylene succinate sebacate formed by succinic acid and / or its derivatives, sebacic acid and / or its derivatives, and 1,4-butanediol has excellent degradability and can meet the requirements for household composting decomposition. However, when succinic acid and sebacic acid react with 1,4-butanediol, oligomers with a degree of polymerization of 1 to 8 are easily produced, resulting in an oligomer content (>4 wt%) in the obtained aliphatic polyester, which can cause food contact hazards as the oligomers are prone to migration and precipitation upon contact with acidic or alcoholic foods. Therefore, those skilled in the art generally tend to reduce the oligomer content. However, the inventors discovered that the presence of oligomers during the processing stage acts as an excellent lubricant, which lowers the viscosity of the system and enables the manufactured packaging film to have excellent unravelability. Accordingly, the present invention controls the molar ratio of succinic acid residues and sebacic acid residues in polybutylene succinate sebacate while simultaneously controlling the oligomer content within the aliphatic polyester within a specific range, thereby enabling the packaging film manufactured from the aliphatic polyester to have excellent unravelability and food contact properties, as well as excellent degradability that meets household composting requirements.
[0009] It must be clarified that the term “residue” above refers to any organic structure introduced into the polymer molecular chain through the condensation reaction of the related monomer, that is, an organic structure derived from the related monomer. For example, a binary residue refers to a structure within an aliphatic polyester derived from a binary monomer.
[0010] In the present invention, the succinic acid derivative comprises an alkyl succinate, and, for example, the alkyl succinate may be at least one of dimethyl succinate, diethyl succinate, di-n-propyl succinate, diisopropyl succinate, di-n-butyl succinate, diisobutyl succinate, di-tert-butyl succinate, di-n-pentyl succinate, diisopentyl succinate, and di-n-hexyl succinate; the alkyl succinate may be an alkyl ester formed from succinic acid or an alkyl ester formed from succinic anhydride, and preferably, dimethyl succinate formed from succinic anhydride is used.
[0011] In the present invention, the sebacic acid derivative comprises an alkyl sebacate; exemplary, the alkyl sebacate may be at least one of dimethyl sebacate, diethyl sebacate, di-n-propyl sebacate, diisopropyl sebacate, di-n-butyl sebacate, diisobutyl sebacate, di-tert-butyl sebacate, di-n-pentyl sebacate, diisopentyl sebacate, and di-n-hexyl sebacate; and the alkyl sebacate may be an alkyl ester formed from sebacic acid or an alkyl ester formed from sebacic acid anhydride.
[0012] In the present invention, the oligomer comprises a linear or cyclic polyester oligomer produced by the reaction of a binary acid and a diol; and also comprises a cyclic oligomer produced by the thermal decomposition of a prepolymer or polycondensate during a prepolymerization or polycondensation process, in which the end groups are "reversed."
[0013] In the present invention, the content of the oligomer can be analyzed using gel permeation chromatography (GPC).
[0014] Preferably, the oligomer in the aliphatic polyester has the following characteristics: 0.05 wt% <q1<1.0 wt%, 0.1 wt%<q2<2.5 wt%을 갖고, q1은 GPC로 측정한 지방족 폴리에스테르 중 수평균 분자량이 500 미만인 올리고머의 질량 백분율이고, q2는 GPC로 측정한 지방족 폴리에스테르 중 수평균 분자량이 1000 미만인 올리고머의 질량 백분율이고; 더욱 바람직하게, 0.08 wt%<q1<0.8 wt%, 0.15 wt%<q2<2.1 wt%이다.
[0015] Preferably, the above q1 is 0.1 to 0.6 wt%.
[0016] Preferably, the above q2 is 0.2 to 1.3 wt%.
[0017] Preferably, the ratio of q2 to q1 is < 2, more preferably the ratio of q2 to q1 is < 1.5, and even more preferably the ratio of q2 to q1 is 1.1 to 1.45.
[0018] Preferably, the binary acid residue comprises the following residues: a1): 70 to 87 mol% of succinic acid residues based on a total molar percentage content of a1) and a2) of 100 mol%; a2): 13 to 30 mol% of sebacic acid residues based on a total molar percentage content of a1) and a2) of 100 mol%; more preferably, the binary acid residue comprises the following residues: a1): 74 to 85 mol% of succinic acid residues based on a total molar percentage content of a1) and a2) of 100 mol%; a2): 15 to 26 mol% of sebacic acid residues based on a total molar percentage content of a1) and a2) of 100 mol%.
[0019] In the present invention, considering the aging resistance, hydrolysis resistance, degradation performance, and cost of the aliphatic polyester, preferably, according to GB / T 32366-2015, the carboxyl group content of the aliphatic polyester is <40 mol / t, more preferably <30 mol / t, even more preferably <22 mol / t, and particularly preferably the carboxyl group content is 8 to 20 mol / t.
[0020] In the present invention, the carboxyl group content can be controlled by adjusting the degree of reaction or suppressing thermal decomposition by changing conditions such as the alcohol-acid ratio, polymerization temperature, and polymerization time. Additionally, the carboxyl group content can be controlled by suppressing the type or amount of impurities, such as nitrogen compounds and metal ions, contained in the raw material.
[0021] Considering production efficiency and mechanical properties of molded parts, preferably, according to GB / T 17931-1999, the intrinsic viscosity of the aliphatic polyester is 1 to 3 dL / g, preferably 1.5 to 2.2 dL / g, more preferably 1.58 to 2.11 dL / g, even more preferably 1.67 to 2.02 dL / g, and particularly preferably 1.82 to 1.95 dL / g.
[0022] In the present invention, the method for producing the aliphatic polyester is not particularly limited, and any method capable of producing an aliphatic polyester having a specific oligomer content of the present invention is permitted. Preferably, the method for producing the aliphatic polyester comprises the following steps:
[0023] (1) A step of obtaining an esterification product by reacting a diol with a diacid;
[0024] (2) A step of obtaining a prepolymerized product by prepolymerizing the esterification product obtained in step (1);
[0025] (3) A step of obtaining the polycondensation product by reacting the prepolymerization product obtained in step (2) with the prepolymerization product;
[0026] (4) A step of obtaining the aliphatic polyester by contacting the polycondensation product obtained in step (3) with an organic solvent.
[0027] In the present invention, in step (1), the diacetate is succinic acid and / or a succinic acid derivative, and sebacic acid and / or a sebacic acid derivative; the diacetate may be used alone or as a mixture of at least two; and the diol is 1,4-butanediol.
[0028] In the present invention, the source of the succinic acid and / or succinic acid derivative is not particularly limited. It may be derived from bio-based succinic acid and / or succinic acid derivatives (i.e., the raw material for production is biomass resources) or petroleum-based succinic acid and / or succinic acid derivatives (i.e., the raw material for production is petroleum resources).
[0029] In the present invention, the molar ratio of the diol and the binary acid in step (1) is (1.2 to 3):1, for example, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1 or any range between the above values, and more preferably (1.4 to 2):1.
[0030] In the present invention, the raw material of the reaction in step (1) further comprises a crosslinking agent; based on 100 wt% of the total mass of the diol and diol, the mass of the crosslinking agent is 0 to 3 wt%; the crosslinking agent comprises at least one of a polyol, a poly acid, or a poly acid anhydride; exemplarily, the crosslinking agent comprises but is not limited to tartaric acid, citric acid, malic acid, trimethylolpropane, trimethylolethane, pentaerythritol, polyethertriol, glycerol, 1,3,5-benzotric acid, 1,2,4-benzotric acid, 1,2,4-benzotric acid anhydride, 1,2,4,5-benzotetratic acid, benzopyrene dianhydride, etc.
[0031] In the present invention, the reaction in step (1) comprises an esterification reaction and / or an ester exchange reaction; the reaction temperature is 140 to 220°C, the pressure is 0.7 to 1.4 bar, and the time is 2 to 5 h, and more preferably the reaction temperature is 165 to 212°C, the pressure is 0.78 to 1.2 bar, and the time is 2.4 to 4.5 h.
[0032] In the present invention, step (1) can be performed in a mixing device, and a slurry is obtained by mixing a diacid and a diol, and then heated to react.
[0033] In the present invention, the carboxyl group content of the esterification product in step (1) is 245 to 575 mol / t, more preferably 310 to 420 mol / t.
[0034] In the present invention, after the reaction of step (1), the excess amount of diol is further removed through distillation, and the removed diol can be purified through distillation and reused as a raw material, and the purity of the purified diol is ≥ 95%.
[0035] In the present invention, in step (2), the prepolymerization reaction temperature is 230 to 260°C, the pressure is 0.3 to 0.8 bar, and the time is 70 to 200 min; more preferably, the reaction temperature is 235 to 246°C, the pressure is 0.35 to 0.65 bar, and the time is 90 to 130 min.
[0036] In the present invention, step (2) can be performed in a single prepolymerization reactor.
[0037] In the present invention, the carboxyl group content of the prepolymerization product in step (2) is 40 to 90 mol / t, more preferably 60 to 80 mol / t.
[0038] In the present invention, in step (3), the polycondensation reaction temperature is 235~260℃, the pressure is 0.2~5 mbar, and the time is 40~110 min; more preferably, the reaction temperature is 238~250℃, the pressure is 0.5~2 mbar, and the time is 48~98 min.
[0039] In the present invention, in step (3), the carboxyl group content of the polycondensation product is <50 mol / t, preferably <35 mol / t, and more preferably 10 to 25 mol / t.
[0040] In the present invention, step (3) can be performed in a suitable polymerization reaction finishing equipment such as a rotary reactor, a cage reactor, or a horizontal reactor.
[0041] In the present invention, the reactions in steps (1), (2), and (3) are each carried out independently in the presence of a catalyst. In steps (1), (2), and (3), the catalyst may be the same or different from one another. The catalyst may be an external catalyst or a catalyst present within the system. The catalyst is a tin compound, an antimony compound, a cobalt compound, a lead compound, a zinc compound, an aluminum compound, or a titanium compound, more preferably a zinc compound, an aluminum compound, or a titanium compound, and most preferably a titanium compound; the titanium compound may be tetrabutyl titanate or tetraisopropyl titanate; the lower the residual amount of the titanium compound compared to other compounds in the product or downstream product, the lower the toxicity. In particular, it is suitable for manufacturing biodegradable polyesters, which can be directly introduced into the environment in the form of compost bags or cover films.
[0042] In the present invention, based on 100 wt% of the total mass of the reaction raw materials (biacid, diol, and optionally a crosslinking agent), the total mass of the catalyst is 0.001 to 1 wt%.
[0043] In the present invention, other auxiliary agents may be added during the reaction of step (3) as needed; said other auxiliary agents include, but are not limited to, catalyst passivating agents, color stabilizers, activators, etc.
[0044] The above-mentioned catalytic passivating agent comprises, but is not limited to, a phosphorus compound; the above-mentioned phosphorus compound comprises, but is not limited to, one or more of phosphoric acid and phosphoric acid; and based on 100 wt% of the mass of the prepolymerization product, the mass of the catalytic passivating agent is 0.001 to 0.1 wt%, preferably 0.01 to 0.05 wt%. For example, when a highly active titanium compound is selected as the catalyst, the catalytic passivating agent may be added, wherein the molar ratio of Ti to P is (1.1 to 1.5):1, and particularly preferably the molar ratio of Ti to P is (1.1 to 1.3):1.
[0045] The above color stabilizer includes, but is not limited to, a phosphorus compound; the above phosphorus compound includes, but is not limited to, one or more of phosphoric acid, phosphorous acid, triphenyl phosphite, triphenyl phosphate, sodium hypophosphite, and sodium phosphate; using a color stabilizer generally reduces the condensation rate. Therefore, preferably, triphenyl phosphate, which does not adversely affect the condensation rate, is used as a color stabilizer. Based on 100 wt% of the mass of the prepolymerization product, the mass of the color stabilizer is 0.001 to 1.5 wt%, preferably 0.01 to 1.0 wt%; and when a titanium compound is used as a catalyst, the molar ratio of Ti to P is 1:(0.3 to 1.0), particularly preferably 1:(0.5 to 1.0).
[0046] The above-mentioned activator comprises, but is not limited to, a phosphorus compound; the phosphorus compound comprises, but is not limited to, one or more of sodium dihydrogen phosphate, calcium hypophosphite, calcium phosphate, calcium phosphate, sodium hypophosphite, sodium phosphate, triphenyl phosphate, triphenyl phosphate, trimethyl phosphate, triethyl phosphate, tripropyl phosphate, and tributyl phosphate. Based on 100 wt% of the mass of the prepolymerization product, the mass of the activator is 0.001 to 1.5 wt%, preferably 0.01 to 1.0 wt%; and when a titanium compound is used as a catalyst, the molar ratio of Ti to P is (1.0 to 1.5):1, particularly preferably the molar ratio of Ti to P is (1.1 to 1.3):1.
[0047] More preferably, a color stabilizer and an active agent are used together, for example, triphenyl phosphate and sodium dihydrogen phosphate are used together.
[0048] In the present invention, a chain growth reaction is further included after the polycondensation reaction, that is, a product obtained through the polycondensation reaction (polycondensation product) is reacted with a chain growth agent to obtain a chain growth product.
[0049] In the present invention, the chain growth agent comprises one or more of isocyanate, peroxide, epoxide, oxazoline, oxazine, caprolactam, or carbodiimide.
[0050] In the present invention, the isocyanate may be an aromatic diisocyanate and / or an aliphatic diisocyanate, and the aromatic diisocyanate may be toluene 2,4-diisocyanate, toluene 2,6-diisocyanate, diphenylmethane 2,2′-diisocyanate, diphenylmethane 2,4′-diisocyanate, diphenylmethane 4,4′-diisocyanate, naphthalene 1,5-diisocyanate or ditoluene diisocyanate; particularly preferably, diphenylmethane 2,2′-diisocyanate, diphenylmethane 2,4′-diisocyanate or diphenylmethane 4,4′-diisocyanate may be used. The above aromatic diisocyanate may be a polycyclic aromatic diisocyanate, for example, tris(4-isocyanate-phenyl)methane having three rings, which may be produced during the process of manufacturing a diisocyanate having one or two rings. The above aliphatic diisocyanate may be a straight-chain or branched alkylene diisocyanate having 2 to 20 carbon atoms or a cycloalkylene diisocyanate having 3 to 20 carbon atoms; exemplarily, the above aliphatic diisocyanate comprises hexamethylene diisocyanate, pentamethylene diisocyanate, isophorone diisocyanate, or methylenebis(4-isocyanate-cyclohexane) diisocyanate. Particularly preferably, it is hexamethylene diisocyanate.
[0051] In the present invention, based on the total mass of the polycondensation product, the mass of the isocyanate may be 0.05 to 2 wt%, and particularly preferably 0.1 to 1.5 wt%.
[0052] In the present invention, the peroxide may be one or more of benzoyl peroxide, 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(tert-butylperoxy)methylcyclododecane, n-butyl 4,4-di(butylperoxy)valerate, dicumyl peroxide, tert-butylperoxybenzoate, dibutyl peroxide, α,α-di(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hex-3-phosphorus, or tert-butylperoxycumene.
[0053] In the present invention, based on the total mass of the polycondensation product, the mass of the peroxide may be 0.1 to 2 wt%, and particularly preferably 0.2 to 1 wt%.
[0054] In the present invention, the epoxide may be one or more of a copolymer containing an epoxy group based on diglycidyl ether, hexamethylene diglycidyl ether, sorbitol diglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, resorcinol diglycidyl ether, neopentyl diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether and polybutanediol diglycidyl ether, styrene, acrylate and / or methyl acrylate.
[0055] In the present invention, based on the total mass of the polycondensation product, the mass of the epoxide may be 0.1 to 2 wt%, and preferably 0.2 to 1 wt%.
[0056] In the present invention, the oxazolin may be selected from one or more of 2,2′-di(2-oxazolin)methane, 1,2-di(2-oxazolin)ethane, 1,3-di(2-oxazolin)propane, 1,4-di(2-oxazolin)butane, 1,4-di(2-oxazolin)benzene, 1,2-di(2-oxazolin)benzene, or 1,3-di(2-oxazolin)benzene. The above oxazine may be selected from one or more of 2,2′-di(2-dioxazine), bis(2-dioxazinyl)methane, 1,2-di(2-dioxazinyl)ethane, 1,3-di(2-dioxazinyl)propane, 1,4-di(2-dioxazinyl)butane, 1,4-di(2-dioxazinyl)benzene, 1,2-di(2-dioxazinyl)benzene, or 1,3-di(2-dioxazinyl)benzene. The above carbodiimide is N,N′-di-2,6-diisopropylphenylcarbodiimide, N,N′-di-o-tolylcarbodiimide, N,N′-diphenylcarbodiimide, N,N′-dioctyldecylcarbodiimide, N,N′-di-2,6-dimethylphenylcarbodiimide, N-tolyl-N′-cyclohexylcarbodiimide, N,N′-di-2,6-di-tert-butylphenylcarbodiimide, N,N′-di-2,4,6-triisobutylphenylcarbodiimide, diisopropylcarbodiimide, dimethylcarbodiimide, diisobutylcarbodiimide, dioctylcarbodiimide, tert-butylisopropylcarbodiimide, di-β-naphthylcarbodiimide, or It can be selected from one or more of di-tert-butylcarbodiimide.
[0057] In the present invention, based on the total mass of the polycondensation product, the mass of the oxazoline, oxazine, caprolactam, and carbodiimide may each be independently 0.1 to 2 wt%, and preferably 0.2 to 1 wt%.
[0058] In the present invention, the chain growth reaction temperature is 170 to 245°C, more preferably the reaction temperature is 180 to 235°C; and depending on the system used, it is carried out under atmospheric pressure or superatmosphere.
[0059] In the present invention, the chain growth reaction may be carried out in an extruder, a continuous kneader (list reactor), or a static mixer. The extruder may be a single-screw extruder or a double-screw extruder, and the static mixer may use SMR, SMX, or SMXL members or a combination thereof. Examples of list reactors include a single-screw DISCOTHERM B, a double-screw CRP, or ORP reactor. Preferably, the chain growth reaction is carried out in an extruder, and the residence time in the extruder is 2 to 15 min, more preferably 4 to 13 min.
[0060] In the present invention, step (4) further includes a step of cutting the polycondensation product before contact treatment, the cutting size is limited to the weight of 100 particles (weight of 100 particles), and after cutting the polycondensation product, the weight of 100 particles is 2.2 to 6.0 g, preferably 3.0 to 4.5 g.
[0061] In the present invention, the mass ratio of the polycondensation product and the organic solvent in step (4) is 1:(1 to 10), and may be, for example, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any range between the above values; more preferably 1:(2 to 6).
[0062] In the present invention, it is preferable to use an organic solvent with a boiling point not exceeding 100°C to facilitate the evaporation of the organic solvent in subsequent processes and to minimize organic solvent residues in the polyester product.
[0063] Preferably, the organic solvent comprises at least one of a ketone compound, an alcohol compound, an ether compound, and an aliphatic hydrocarbon compound; the ketone compound comprises but is not limited to acetone and / or butanone, and is preferably acetone; the alcohol compound comprises but is not limited to methanol, ethanol, isopropanol, etc.; the ether compound comprises but is not limited to ethyl ether, propyl ether, and tetrahydrofuran, and is preferably tetrahydrofuran; and the aliphatic hydrocarbon compound comprises but is not limited to at least one of n-hexane, n-heptane, and cyclohexane, and is preferably n-hexane and / or cyclohexane.
[0064] In the present invention, the organic solvent may be a pure organic solvent or an aqueous organic solvent solution; and when selected from an aqueous organic solvent solution, the mass concentration of the aqueous organic solvent solution is 35 to 90 wt%.
[0065] In the present invention, in step (4), the temperature of the contact treatment is 35 to 80°C and the time is 3 to 20 h; preferably, the temperature of the contact treatment is 40 to 55°C and the time is 8 to 18 h.
[0066] In the present invention, the oligomer content in an aliphatic polyester can be controlled through contact treatment. Specifically, the oligomer content can be controlled by controlling the temperature, time, and mass ratio of the polycondensation product to the organic solvent during contact treatment; if the contact treatment temperature is too high, the organic solvent evaporates rapidly, resulting in significant loss; if the contact treatment temperature is too low, the elution effect does not appear effectively, leading to an excessively high oligomer content. If the contact treatment time is too long, the amount of organic solvent remaining in the polyester increases, and if the contact treatment time is too short, the elution effect does not appear effectively, leading to an excessively high oligomer content. If the mass ratio of the polycondensation product to the organic solvent deviates from the appropriate range, that is, if the organic solvent content is too high, the elution effect is effectively enhanced, but more solvent is required, the amount of waste liquid generated increases, reducing economic efficiency, and the amount of organic solvent remaining in the polyester increases; if the content is too low, uniform dispersion of the polyester within the solution is not achieved, resulting in non-uniformity and a non-uniform elution effect, which leads to a decrease in the elution effect.
[0067] In addition to the contact treatment of step (4), the polymerization conditions and alcohol-acid ratio of steps (1) to (3) all affect the oligomer content.
[0068] In the present invention, the method for manufacturing the aliphatic polyester may be to manufacture it through contact treatment of a polycondensation product, or through a chain extension reaction (i.e., a chain growth reaction) of the polycondensation product; or to manufacture it by first chain-extending the polycondensation product and then performing contact treatment.
[0069] In the present invention, the aliphatic polyester can also be produced by a method in which succinic acid and / or a succinic acid derivative and sebacic acid and / or a sebacic acid derivative are each reacted with 1,4-butanediol in step (1) to obtain two esterified products, and then the two esterified products are subjected to a subsequent prepolymerization reaction, a polycondensation reaction, and an optional chain growth reaction and contact treatment.
[0070] For example, the above manufacturing method specifically comprises the following steps:
[0071] Step (1-1): A step of reacting succinic acid and / or a succinic acid derivative, 1,4-butanediol, with a selective crosslinking agent for 2 to 6 hours under conditions of a temperature of 150 to 195°C and a pressure of 0.7 to 1.2 bar to obtain esterification product A;
[0072] Step (1-2): Sebacic acid and / or a sebacic acid derivative are reacted with 1,4-butanediol at a temperature of 180–220°C and a pressure of 0.6–1.1 bar for 2–6 hours to obtain esterification product B; then, esterification product A and esterification product B are mixed and subjected to a prepolymerization reaction, a polycondensation reaction, an optional chain growth reaction, and a contact treatment; wherein the conditions of the prepolymerization reaction, the polycondensation reaction, the optional chain growth reaction, and the contact treatment are selected from the same range as in Step (2), Step (3), the aforementioned chain growth reaction, and Step (4).
[0073] In a second aspect, the present invention provides a polyester composition, said polyester composition comprises an aliphatic polyester according to a first aspect.
[0074] Preferably, the polyester composition further comprises at least one of a second polyester, a third polymer, and an auxiliary agent.
[0075] Preferably, the second polyester comprises at least one of polylactic acid, an aliphatic-aromatic polyester, or other aliphatic polyesters.
[0076] Preferably, the second polyester comprises at least one of polylactic acid (PLA), an aliphatic-aromatic polyester, or other aliphatic polyesters.
[0077] Preferably, it comprises at least one of the aliphatic-aromatic polyester polybutylene terephthalate (PBST), polybutylene adipate terephthalate (PBAT), polybutylene sebacate terephthalate (PBSeT), or polybutylene adipate furandicarboxylate (PBAF).
[0078] Preferably, the other aliphatic polyester comprises at least one of polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), or polybutylene sebacate (PBSe).
[0079] In the present invention, according to the ISO 1133-2-2012 standard, the melt flow rate of the second polyester is 0.5 to 50 g / 10 min under conditions of 190°C and 2.16 kg.
[0080] In the present invention, the second polyester may be selected from among suitable polyesters according to actual needs and is not limited to the polyesters mentioned above.
[0081] Preferably, the third polymer comprises at least one of starch, cellulose, chitin, chitosan, alginate ester, protein, gelatin, natural rubber, lignin, or a derivative of the aforementioned material.
[0082] In the present invention, the protein includes, but is not limited to, gluten, zein, casein, collagen, etc. The lignin includes unrefined lignin, refined hydrolyzed lignin, alkalized lignin, etc. Starch may also be used in an allosteric form, a gelled form, or as a filler. The starch may exist in a continuous phase or a dispersed phase, or in a form where both phases coexist.
[0083] In the present invention, the auxiliary agent may be added as needed and includes, but is not limited to, at least one of an antioxidant, a lubricant, a light stabilizer, a release agent, or an antistatic agent.
[0084] In the present invention, the type of auxiliary agent is not overly limited, and conventional additives are sufficient. For example, the antioxidant comprises, but is not limited to, any one of antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 164, antioxidant DLTP, or antioxidant TPP.
[0085] The above light stabilizer includes, but is not limited to, at least one of hindered amine-based light stabilizers (e.g., light stabilizer 770, light stabilizer 622, light stabilizer 944, etc.), benzophenone-based light stabilizers (e.g., UV531), or benzotriazole-based light stabilizers.
[0086] The above lubricant includes, but is not limited to, at least one of ester-based (e.g., polyethylene glycol ester, polyol ester), lignite salt, ethylene bis-stearamide, or polyethylene wax.
[0087] The above-mentioned release agent includes, but is not limited to, at least one of an inorganic release agent (e.g., talc powder, mica powder, clay, etc.), an organic release agent (e.g., fatty acids, paraffin wax, glycerin, and petroleum jelly, etc.), or a polymeric release agent (e.g., silicone oil, polyethylene glycol, and low molecular weight polyethylene, etc.).
[0088] The above antistatic agent comprises, but is not limited to, at least one of a cationic antistatic agent (e.g., quaternary ammonium salt), anionic antistatic agent (e.g., alkylsulfonate, phosphate), amphoteric antistatic agent (e.g., amphoteric imidazoline compound), nonionic antistatic agent (e.g., hydroxyethylalkylamine, fatty amide, polyoxyethylene, polyol ester), or polymeric antistatic agent (e.g., polyether).
[0089] As a preferred technical embodiment of the present invention, based on weight parts, the polyester composition comprises 50 to 95 parts of an aliphatic polyester (e.g., 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or any range between these values, preferably 52 to 92 parts, more preferably 56 to 82 parts), 1 to 20 parts of a second polyester (e.g., 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, or any range between these values, preferably 1.5 to 15 parts, more preferably 2.5 to 8.5 parts), 1 to 30 parts of a third polymer (e.g., 1, 2, 4, 6, 8, It includes 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 25 parts, 26 parts, 28 parts, 30 parts, or any range between the above values, preferably 9 to 27 parts, more preferably 21 to 26.5 parts) and 0 to 15 parts of an auxiliary agent (e.g., 1 part, 2 parts, 4 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 15 parts, or any range between the above values).
[0090] In the present invention, the method for preparing the polyester composition comprises the step of mixing an aliphatic polyester with an optional second polyester, a third polymer, and an auxiliary agent, and extruding to obtain the polyester composition, wherein the extruder may be a reactive extruder, and the extruder may be a single-screw extruder, a double-screw extruder, or a multi-screw extruder; the temperature of the extrusion is 140 to 220°C, and the screw rotation speed during extrusion is 200 to 500 rpm.
[0091] In a second aspect, the present invention provides a packaging film, said packaging film being manufactured using a raw material comprising an aliphatic polyester according to the first aspect or a polyester composition according to the second aspect.
[0092] In the present invention, the raw materials for manufacturing the packaging film may also include other materials, such as coloring agents, pigments, and inorganic fillers, depending on actual needs; the pigments include, but are not limited to, titanium white powder; and the inorganic fillers include, but are not limited to, talc powder, calcium carbonate, kaolin.
[0093] Preferably, the unwinding index of the packaging film is ≤3, more preferably ≤2.5, even more preferably ≤2, and particularly preferably ≤1.5.
[0094] Preferably, according to the EU10-2011 standard, under OM6 test conditions, using 10% ethanol as a mock solution, and under conditions where the thickness of the packaging film is 18±2 μm, the total migration amount of said packaging film ≤ 10 mg / dm 2 , more preferably total transfer amount ≤ 5 mg / dm 2 am.
[0095] In the present invention, the packaging film includes a food preservation film, a shrink film, a stretch film, etc.
[0096] The aliphatic polyester of the present invention, the polyester composition comprising the aliphatic polyester, and the packaging film prepared therefrom are all biodegradable.
[0097] For the purposes of the present invention, a material or mixture of materials is considered to have "biodegradable" if it has a biodegradability of 90% or more as defined in DIN EN 13432.
[0098] According to DIN EN 13432, during the composting process, air from which CO2 has been removed is injected into the matured compost, and the compost undergoes a specific temperature process. Here, biodegradability is defined as a percentage of the degree of biodegradation, expressed as the value obtained by dividing the net amount of CO2 emitted from the sample (minus the amount of CO2 emitted from the compost without the sample) by the maximum amount of CO2 that the sample can emit (calculated from the carbon content of the sample). Biodegradable polyesters and biodegradable polyester compositions generally show clear signs of degradation, such as mold growth, dissolution, and perforation, within a few days after composting.
[0099] Other methods for measuring biodegradability are also described in ASTM D5338 and ASTM D6400.
[0100] The numerical range of the present invention includes specific values between the points listed above as well as the values not listed above; however, for the sake of breadth constraints and brevity, the present invention does not enumerate all specific values included in the range. Effects of the invention
[0101] Compared to existing technology, the present invention has the following beneficial effects.
[0102] The aliphatic polyester provided in the present invention controls the molar ratio of succinic acid and sebacic acid within a specific range and simultaneously controls the oligomer content within the aliphatic polyester within a specific range, thereby allowing the packaging film containing the aliphatic polyester to not only have excellent unravelability and food contact properties but also exhibit excellent degradability, satisfying the requirements for household composting. Specific details for implementing the invention
[0103] The technical solution of the present invention will be described in more detail below through specific embodiments. Those skilled in the art should understand that the described embodiments are merely for the purpose of facilitating an understanding of the present invention and should not be construed as specific limitations of the invention.
[0104] All materials used in the present invention may be commercially available products or manufactured using conventional manufacturing methods. Unless otherwise specified, the materials used in the present invention are as follows.
[0105] 1,4-Butanediol: Purchased from Xinjiang Meiji Chemical Co., Ltd.
[0106] Succinic acid: Purchased from Shandong Landian Biotechnology Co., Ltd.
[0107] Sebacic acid: Purchased from Hengshui Jinghua Chemical Co., Ltd.
[0108] Glycerol: Purchased from Aladdin.
[0109] Tetrabutyl titanate: Purchased from Zeni Chemical Import & Export Co., Ltd.
[0110] Hexamethylene diisocyanate: Purchased from Aladdin.
[0111] In the present invention, the method for measuring the molar content of succinic acid residues and sebacic acid residues, number average molecular weight (Mn), oligomer content, intrinsic viscosity, and carboxyl group content in an aliphatic polyester is as follows.
[0112] 1. The molar content of succinic acid residues and sebacic acid residues in aliphatic polyesters is 1Measurements were performed using the H NMR method. Specifically, 20 mg of the above-mentioned aliphatic polyester sample was dissolved in 0.6 mL of deuterated chloroform, and then the 1H NMR spectrum was measured at room temperature using a Bruker AV 500 NMR spectrometer. The characteristic peaks of succinic acid residues and sebacic acid residues were integrated, and the percentage of peak area was calculated to determine the molar content of succinic acid residues and sebacic acid residues in the aliphatic polyester, respectively. It should be noted that the content of succinic acid residues and sebacic acid residues in the aliphatic polyester presented in Table 1 was calculated by setting the total molar amount of succinic acid residues and sebacic acid residues to 100 mol%. For example, when the integral area of the succinic acid residue is I1 and the integral area of the sebacic acid residue is I2, the molar percentage content of succinic acid in the aliphatic polyester is I1 / (I1+I2)×100%, where the characteristic chemical shift of the succinic acid residue is about 2.63 ppm, representing four hydrogen atoms in the two methylene-CH2-CH2- of succinic acid. The characteristic chemical shift of the sebacic acid residue is about 1.30 ppm, representing eight hydrogen atoms in the four methylene-CH2-CH2-CH2- of the center of sebacic acid.
[0113] 2. Mn and oligomer content were measured using gel permeation chromatography (GPC). The chromatography system was used at 40°C, and three serial columns (particle diameter 5 μm, pore size 500 each) were used. , 1000 , 10000 A refractive index detector was used. Chloroform was used as the eluent (elution flow rate 1 mL / min), and polystyrene was used as the standard. The instrument model was a Waters 1515GPC. For sample preparation, an aliphatic polyester was directly dissolved in chromatography-grade THF to prepare a 1 mg / mL solution for measurement.
[0114] 3. The intrinsic viscosity test was conducted according to the GB / T 17931-1999 standard. Specifically, 0.1250±0.0002g of the sample was added to 25mL of a phenol / o-dichlorobenzene mixed solution in a weight ratio of 1:1, and heated until the sample was completely dissolved. Once the sample was completely dissolved, the viscosity was measured using an Ubérod viscometer at a measurement temperature of 25±0.05℃.
[0115] 4. The carboxyl group content test was conducted according to the GB / T 32366-2015 standard. Specifically, 1 g of the sample was dissolved in 50 mL of a phenol / trichloromethane mixed solution with a volume ratio of 2:3. A potassium hydroxide ethanol solution with a concentration of 0.01 mol / L was used as the standard titration solution, and a bromophenol blue solution with a concentration of 0.2% was used as the indicator. A blank test was performed according to the method for measuring the carboxyl group content of the sample. The sample was tested twice in parallel, and the difference between the two test results must be 2 mol / t or less. The final result was the average of the two test results.
[0117] Examples 1–16, Comparative Examples 1–6
[0118] Examples 1 to 16 and Comparative Examples 1 to 6 each provide an aliphatic polyester, and the molecular structure, q1 and q2 values, carboxyl group content, and intrinsic viscosity of the aliphatic polyester are shown in Table 1.
[0119] [Table 1]
[0120]
[0121] The method for manufacturing the aliphatic polyester provided in Examples 1 to 16 and Comparative Examples 1 to 6 is as follows.
[0122] Example 1
[0123] A method for manufacturing the above-mentioned aliphatic polyester is provided, specifically comprising the following steps.
[0124] (1) 479 kg of succinic acid, 116 kg of sebacic acid, 560 kg of 1,4-butanediol and 2.46 kg of glycerol were physically mixed, and after mixing was complete, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 3.5 hours under conditions of a temperature of 200°C and a pressure of 1.1 bar to obtain an esterification product.
[0125] (2) The esterification product obtained in step (1) was transferred to a vertical reactor with stirring, 0.48 kg of tetrabutyl titanate was added, and a prepolymerization reaction was carried out for 120 minutes at a temperature of 240°C and a pressure of 0.52 bar to obtain a prepolymerization product.
[0126] (3) The prepolymerization product obtained in step (2) was transferred to a horizontal reactor under stirring, and the polycondensation reaction was carried out for 90 minutes under conditions of a temperature of 243°C and a pressure of 1.3 mbar to obtain the polycondensation product.
[0127] (4) The polycondensation product obtained in step (3) is cut, and the weight of 100 particles of the section is about 3.7 g, and a contact treatment process is performed with an aqueous tetrahydrofuran solution; wherein the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution is 1:5, the mass concentration of the aqueous tetrahydrofuran solution is 70%, the contact treatment temperature is 50°C, and the contact treatment time is 14 hours, thereby obtaining the aliphatic polyester.
[0128] Example 2
[0129] A method for manufacturing the above-mentioned aliphatic polyester is provided, specifically comprising the following steps.
[0130] (1) 433 kg of succinic acid, 162 kg of sebacic acid, 570 kg of 1,4-butanediol and 2.46 kg of glycerol were physically mixed, and after mixing was complete, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 4 hours at a temperature of 190 ℃ and a pressure of 0.9 bar to obtain an esterification product.
[0131] (2) The esterification product obtained in step (1) was transferred to a vertical reactor being stirred, 0.48 kg of tetrabutyl titanate was added, and a prepolymerization reaction was carried out for 110 minutes at a temperature of 243°C and a pressure of 0.45 bar to obtain a prepolymerization product.
[0132] (3) The prepolymerization product obtained in step (2) was transferred to a horizontal reactor under stirring, and the polycondensation reaction was carried out for 80 minutes under conditions of a temperature of 243°C and a pressure of 1.1 mbar to obtain the polycondensation product.
[0133] (4) The polycondensation product obtained in step (3) is cut, and the weight of 100 particles of the section is about 3.7 g, and a contact treatment process is performed with an aqueous tetrahydrofuran solution; wherein the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution is 1:5, the mass concentration of the aqueous tetrahydrofuran solution is 65%, the contact treatment temperature is 55°C, and the contact treatment time is 14 hours, thereby obtaining the aliphatic polyester.
[0134] Example 3
[0135] A method for manufacturing the above-mentioned aliphatic polyester is provided, specifically comprising the following steps.
[0136] (1) 388 kg of succinic acid, 215 kg of sebacic acid, 560 kg of 1,4-butanediol and 2.46 kg of glycerol were physically mixed, and after mixing was complete, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 4 hours at a temperature of 205°C and a pressure of 1.0 bar to obtain an esterification product.
[0137] (2) The esterification product obtained in step (1) was transferred to a vertical reactor with stirring, 0.48 kg of tetrabutyl titanate was added, and a prepolymerization reaction was carried out for 95 minutes under conditions of a temperature of 238°C and a pressure of 0.40 bar to obtain a prepolymerization product.
[0138] (3) The prepolymerization product obtained in step (2) was transferred to a horizontal reactor with stirring, and the polycondensation reaction was carried out for 80 minutes under conditions of a temperature of 242°C and a pressure of 1.0 mbar to obtain the polycondensation product.
[0139] (4) The polycondensation product obtained in step (3) is cut, and the weight of 100 particles of the section is about 3.7 g, and a contact treatment process is performed with an aqueous tetrahydrofuran solution; wherein the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution is 1:5, the mass concentration of the aqueous tetrahydrofuran solution is 70%, the contact treatment temperature is 50°C, and the contact treatment time is 14 hours, thereby obtaining the aliphatic polyester.
[0140] Example 4
[0141] A method for manufacturing the above-mentioned aliphatic polyester is provided, specifically comprising the following steps.
[0142] (1) 350 kg of succinic acid, 250 kg of sebacic acid, 534 kg of 1,4-butanediol and 2.46 kg of glycerol were physically mixed, and after mixing was complete, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 3.5 hours under conditions of a temperature of 200°C and a pressure of 1.1 bar to obtain an esterification product.
[0143] (2) The esterification product obtained in step (1) was transferred to a vertical reactor being stirred, 0.48 kg of tetrabutyl titanate was added, and a prepolymerization reaction was carried out for 100 minutes at a temperature of 242°C and a pressure of 0.4 bar to obtain a prepolymerization product.
[0144] (3) The prepolymerization product obtained in step (2) was transferred to a horizontal reactor under stirring, and the polycondensation reaction was carried out for 85 minutes under conditions of a temperature of 242°C and a pressure of 1.1 mbar to obtain the polycondensation product.
[0145] (4) The polycondensation product obtained in step (3) is cut, and the weight of 100 particles of the section is about 3.7 g, and a contact treatment process is performed with an aqueous tetrahydrofuran solution; wherein the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution is 1:5, the mass concentration of the aqueous tetrahydrofuran solution is 70%, the contact treatment temperature is 50°C, and the contact treatment time is 14 hours, thereby obtaining the aliphatic polyester.
[0146] Example 5
[0147] A method for manufacturing the above-mentioned aliphatic polyester is provided, specifically comprising the following steps.
[0148] (1) 320 kg of succinic acid, 280 kg of sebacic acid, 534 kg of 1,4-butanediol and 2.46 kg of glycerol were physically mixed, and after mixing was complete, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 3 hours at a temperature of 180°C and a pressure of 0.8 bar to obtain an esterification product.
[0149] (2) The esterification product obtained in step (1) was transferred to a vertical reactor with stirring, 0.48 kg of tetrabutyl titanate was added, and a prepolymerization reaction was carried out for 110 minutes at a temperature of 243°C and a pressure of 0.60 bar to obtain a prepolymerization product.
[0150] (3) The prepolymerization product obtained in step (2) was transferred to a horizontal reactor under stirring, and the polycondensation reaction was carried out for 90 minutes under conditions of a temperature of 243°C and a pressure of 1.3 mbar to obtain the polycondensation product.
[0151] (4) The polycondensation product obtained in step (3) is cut, and the weight of 100 particles of the section is about 3.7 g, and a contact treatment process is performed with an aqueous tetrahydrofuran solution; wherein the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution is 1:4, the mass concentration of the aqueous tetrahydrofuran solution is 60%, the contact treatment temperature is 45°C, and the contact treatment time is 12 hours, thereby obtaining the aliphatic polyester.
[0152] Example 6
[0153] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, the difference from Example 4 being that in step (3), the prepolymerization product obtained in step (2) is transferred to a horizontal reactor under stirring and a polycondensation reaction is carried out for 60 minutes under conditions of a temperature of 240°C and a pressure of 1.4 mbar to obtain a polycondensation product, after which the polycondensation product and hexamethylene diisocyanate (content of 0.20 wt% of the mass of the polycondensation product) are extruded in a reactive extruder at a temperature of 200°C with a residence time of 7 minutes, thereby obtaining a chain growth product fragment, the weight of 100 particles of the fragment is about 3.7 g; and in step (4), a contact treatment process is performed with the chain growth product fragment obtained in step (4) and an aqueous tetrahydrofuran solution; Here, the mass ratio of the chain growth product fragment to the tetrahydrofuran aqueous solution is 1:6, the mass concentration of the tetrahydrofuran aqueous solution is 80%, the contact treatment temperature is 50°C, and the contact treatment time is 15 hours, thereby obtaining the aliphatic polyester; other raw materials, usage amounts, and manufacturing methods are all the same as in Example 4.
[0154] Example 7
[0155] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, the difference from Example 4 is that in step (4), the polycondensation product obtained in step (3) is cut, the weight of 100 particles of the cut is about 3.7 g, and a contact treatment process with an aqueous tetrahydrofuran solution is performed; wherein the mass ratio of the polycondensation product cut to the aqueous tetrahydrofuran solution is 1:8, the mass concentration of the aqueous tetrahydrofuran solution is 85%, the contact treatment temperature is 55°C, and the contact treatment time is 16 hours, thereby obtaining the above-mentioned aliphatic polyester; and other raw materials, usage amounts, and manufacturing methods are all the same as in Example 4.
[0156] Example 8
[0157] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, the difference from Example 4 being that in step (4), the polycondensation product obtained in step (3) is cut, the weight of 100 particles of the cut is about 3.7 g, and a contact treatment process with an aqueous acetone solution is performed; wherein the mass ratio of the polycondensation product to the aqueous acetone solution is 1:5, the mass concentration of the aqueous acetone solution is 75%, the contact treatment temperature is 45°C, and the contact treatment time is 12 hours, thereby obtaining the above-mentioned aliphatic polyester; and other raw materials, usage amounts, and manufacturing methods are all the same as in Example 4.
[0158] Example 9
[0159] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, the difference from Example 4 is that in step (4), the polycondensation product obtained in step (3) is cut, the weight of 100 particles of the cut is about 3.7 g, and a contact treatment process with an aqueous ethanol solution is performed; wherein the mass ratio of the polycondensation product to the aqueous ethanol solution is 1:5, the mass concentration of the aqueous ethanol solution is 80%, the contact treatment temperature is 70°C, and the contact treatment time is 18 hours, thereby obtaining the above-mentioned aliphatic polyester; and other raw materials, usage amounts, and manufacturing methods are all the same as in Example 4.
[0160] Example 10
[0161] A method for manufacturing the above-mentioned aliphatic polyester is provided, comprising the following steps.
[0162] (1) 350 kg of succinic acid, 250 kg of sebacic acid, 534 kg of 1,4-butanediol and 2.46 kg of glycerol were physically mixed, and after mixing was complete, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 2.5 hours at a temperature of 180°C and a pressure of 1.1 bar to obtain an esterification product.
[0163] (2) The esterification product obtained in step (1) was transferred to a vertical reactor being stirred, 0.48 kg of tetrabutyl titanate was added, and a prepolymerization reaction was carried out for 100 minutes at a temperature of 240°C and a pressure of 0.45 bar to obtain a prepolymerization product.
[0164] (3) The prepolymerization product obtained in step (2) was transferred to a horizontal reactor under stirring, and the polycondensation reaction was carried out for 95 minutes under conditions of a temperature of 245°C and a pressure of 1.3 mbar to obtain the polycondensation product.
[0165] (4) The polycondensation product obtained in step (3) is cut, and the weight of 100 particles of the section is about 4.4 g, and a contact treatment process is performed with an aqueous tetrahydrofuran solution; wherein the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution is 1:3, the mass concentration of the aqueous tetrahydrofuran solution is 75%, the contact treatment temperature is 55°C, and the contact treatment time is 12 hours, thereby obtaining the aliphatic polyester.
[0166] Example 11
[0167] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, the difference from Example 4 being that in step (3), the prepolymerization product obtained in step (2) is transferred to a horizontal reactor under stirring and a polycondensation reaction is carried out for 85 minutes under conditions of a temperature of 242°C and a pressure of 1.1 mbar to obtain a polycondensation product, and in step (4), the polycondensation product obtained in step (3) is cut, the weight of 100 particles of the section is about 3.7 g, and a contact treatment process is performed with an aqueous tetrahydrofuran solution; wherein the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution is 1:7, the mass concentration of the aqueous tetrahydrofuran solution is 75%, the contact treatment temperature is 55°C, and the contact treatment time is 14 hours, thereby obtaining the above-mentioned aliphatic polyester; and other raw materials, usage amounts, and manufacturing methods are all the same as in Example 4.
[0168] Example 12
[0169] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, the difference from Example 4 being that in step (3), the prepolymerization product obtained in step (2) is transferred to a horizontal reactor under stirring and a polycondensation reaction is carried out for 50 minutes under conditions of a temperature of 246°C and a pressure of 1.4 mbar to obtain a polycondensation product, and the polycondensation product and hexamethylene diisocyanate (content of 0.55 wt% of the mass of the polycondensation product) are extruded in a reactive extruder at a temperature of 210°C with a residence time of 9 minutes to obtain a chain growth product fragment; in step (4), the chain growth product obtained in step (3) is cut, the weight of 100 particles of the fragment is about 4.0 g, and a contact treatment process with an aqueous ethanol solution is performed; Here, the mass ratio of the chain growth product fragment to the aqueous ethanol solution was 1:4, the mass concentration of the aqueous ethanol solution was 70%, the contact treatment temperature was 50°C, and the contact treatment time was 12 hours, thereby obtaining the aliphatic polyester; other raw materials, usage amounts, and manufacturing methods were all the same as in Example 4.
[0170] Example 13
[0171] The above method for manufacturing an aliphatic polyester is provided, and the difference from Example 4 is,
[0172] (1-1) 350 kg of succinic acid, 290 kg of 1,4-butanediol, and 2.76 kg of glycerol were physically mixed, and after mixing was complete, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 4 hours at a temperature of 170°C and a pressure of 1.1 bar to obtain esterification product A.
[0173] (1-2) 245 kg of sebacic acid and 260 kg of 1,4-butanediol were physically mixed, and after the mixing was completed, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 3 hours at a temperature of 210°C and a pressure of 1.0 bar to obtain esterification product B; after mixing esterification product A and esterification product B, steps (2), (3), and (4) were performed, and other raw materials, usage amounts and manufacturing methods were all the same as in Example 4.
[0174] Example 14
[0175] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, the difference from Example 4 is that in step (4), the polycondensation product obtained in step (3) is cut, the weight of 100 particles of the cut is about 3.7 g, and a contact treatment process with a cyclohexane solution is performed; wherein the mass ratio of the polycondensation product to the cyclohexane solution is 1:8, the mass concentration of the cyclohexane solution is 100%, the contact treatment temperature is 70°C, and the contact treatment time is 16 hours, thereby obtaining the above-mentioned aliphatic polyester; and other raw materials, usage amounts, and manufacturing methods are all the same as in Example 4.
[0176] Example 15
[0177] A method for manufacturing the above-mentioned aliphatic polyester is provided, comprising the following steps.
[0178] (1-1) 350 kg of succinic acid, 310 kg of 1,4-butanediol, and 3.25 kg of glycerol were physically mixed, and after mixing was complete, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 4 hours at a temperature of 190°C and a pressure of 0.9 bar to obtain esterification product A.
[0179] (1-2) 245 kg of sebacic acid and 290 kg of 1,4-butanediol were physically mixed, and after mixing was complete, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 4 hours at a temperature of 210°C and a pressure of 0.8 bar to obtain esterification product B.
[0180] (2) The esterification product A obtained in step (1-1) and the esterification product B obtained in step (1-2) were transferred to a vertical reactor under stirring, 0.48 kg of tetrabutyl titanate was added, and a prepolymerization reaction was carried out for 100 minutes under conditions of a temperature of 240°C and a pressure of 0.5 bar to obtain a prepolymerization product.
[0181] (3) The prepolymerization product obtained in step (2) was transferred to a horizontal reactor with stirring, and the polycondensation reaction was carried out for 90 minutes under conditions of a temperature of 245°C and a pressure of 1.0 mbar to obtain the polycondensation product.
[0182] (4) The polycondensation product obtained in step (3) is cut, and the weight of 100 particles of the section is about 3.2 g, and a contact treatment process is performed with a tetrahydrofuran solution; wherein the mass ratio of the polycondensation product to the tetrahydrofuran solution is 1:6, the mass concentration of the tetrahydrofuran solution is 100%, the contact treatment temperature is 55°C, and the contact treatment time is 18 hours, thereby obtaining the aliphatic polyester.
[0183] Example 16
[0184] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, the difference from Example 4 being that in step (3), the prepolymerization product obtained in step (2) is transferred to a horizontal reactor under stirring and a polycondensation reaction is carried out for 70 minutes under conditions of a temperature of 242°C and a pressure of 1.4 mbar to obtain a polycondensation product, and the polycondensation product and hexamethylene diisocyanate (content of 0.72 wt% of the mass of the polycondensation product) are extruded in a reactive extruder at a temperature of 230°C with a residence time of 12 minutes to obtain a chain growth product fragment; in step (4), the obtained chain growth product is cut, the weight of 100 particles of the fragment is about 4.4 g, and a contact treatment process with an aqueous ethanol solution is performed; Here, the mass ratio of the chain growth product fragment to the aqueous ethanol solution is 1:4, the mass concentration of the aqueous ethanol solution is 65%, the contact treatment temperature is 65°C, and the contact treatment time is 10 hours, thereby obtaining the aliphatic polyester; other raw materials, usage amounts, and manufacturing methods are all the same as in Example 4.
[0185] Comparative Example 1
[0186] The above method for manufacturing an aliphatic polyester is provided, and the difference from Example 4 is that step (4) was not performed; other raw materials, usage amounts, and manufacturing method are all the same as in Example 4.
[0187] Comparative Example 2
[0188] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, the difference from Example 4 being that in step (4), the polycondensation product obtained in step (3) is cut, the weight of 100 particles of the cut is about 3.7 g, and a contact treatment process with an aqueous tetrahydrofuran solution is performed; wherein the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution is 1:10, the mass concentration of the aqueous tetrahydrofuran solution is 85%, the contact treatment temperature is 55°C, and the contact treatment time is 20 hours, thereby obtaining the above-mentioned aliphatic polyester; and other raw materials, usage amounts, and manufacturing methods are all the same as in Example 4.
[0189] Comparative Example 3
[0190] A method for manufacturing the above-mentioned aliphatic polyester is provided, specifically comprising the following steps.
[0191] (1) 275 kg of succinic acid, 315 kg of sebacic acid, 534 kg of 1,4-butanediol and 2.46 kg of glycerol were physically mixed, and after mixing was complete, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 3 hours under conditions of a temperature of 200°C and a pressure of 1.0 bar to obtain an esterification product.
[0192] (2) The esterification product obtained in step (1) was transferred to a vertical reactor with stirring, 0.48 kg of tetrabutyl titanate was added, and a prepolymerization reaction was carried out for 115 minutes at a temperature of 240°C and a pressure of 0.70 bar to obtain a prepolymerization product.
[0193] (3) The prepolymerization product obtained in step (2) was transferred to a horizontal reactor under stirring, and a polycondensation reaction was carried out for 100 minutes under conditions of a temperature of 246°C and a pressure of 1.1 mbar to obtain a polycondensation product.
[0194] (4) The polycondensation product obtained in step (3) is cut, and the weight of 100 particles of the section is about 3.7 g, and a contact treatment process is performed with an aqueous tetrahydrofuran solution; wherein the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution is 1:5, the mass concentration of the aqueous tetrahydrofuran solution is 70%, the contact treatment temperature is 50°C, and the contact treatment time is 14 hours, thereby obtaining the aliphatic polyester.
[0195] Comparative Example 4
[0196] A method for manufacturing the above-mentioned aliphatic polyester is provided, specifically comprising the following steps.
[0197] (1) 535 kg of succinic acid, 60 kg of sebacic acid, 534 kg of 1,4-butanediol and 2.46 kg of glycerol were physically mixed, and after mixing was complete, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 3.5 hours under conditions of a temperature of 200°C and a pressure of 1.1 bar to obtain an esterification product.
[0198] (2) The esterification product obtained in step (1) was transferred to a vertical reactor with stirring, 0.48 kg of tetrabutyl titanate was added, and a prepolymerization reaction was carried out for 120 minutes at a temperature of 243°C and a pressure of 0.50 bar to obtain a prepolymerization product.
[0199] (3) The prepolymerization product obtained in step (2) was transferred to a horizontal reactor with stirring, and the polycondensation reaction was carried out for 90 minutes under conditions of a temperature of 245°C and a pressure of 1.2 mbar to obtain the polycondensation product.
[0200] (4) The polycondensation product obtained in step (3) is cut, and the weight of 100 particles of the section is about 3.7 g, and a contact treatment process is performed with an aqueous tetrahydrofuran solution; wherein the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution is 1:5, the mass concentration of the aqueous tetrahydrofuran solution is 70%, the contact treatment temperature is 50°C, and the contact treatment time is 14 hours, thereby obtaining the aliphatic polyester.
[0201] Comparative Example 5
[0202] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, the difference from Comparative Example 3 is that in step (4), the polycondensation product obtained in step (3) is cut, the weight of 100 particles of the cut is about 3.2 g, and a contact treatment process with an aqueous tetrahydrofuran solution is performed; wherein the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution is 1:8, the mass concentration of the aqueous tetrahydrofuran solution is 90%, the contact treatment temperature is 55°C, and the contact treatment time is 16 hours, thereby obtaining the above-mentioned aliphatic polyester; and other raw materials, usage amounts, and manufacturing methods are all the same as those in Comparative Example 3.
[0203] Comparative Example 6
[0204] The above method for manufacturing an aliphatic polyester is provided, and the difference from Comparative Example 4 is that in step (4), the polycondensation product obtained in step (3) is cut, the weight of 100 particles of the cut is about 3.0 g, and a contact treatment process with an aqueous ethanol solution is performed; wherein the mass ratio of the polycondensation product to the aqueous ethanol solution is 1:8, the mass concentration of the aqueous ethanol solution is 70%, the contact treatment temperature is 70°C, and the contact treatment time is 18 hours, thereby obtaining the aliphatic polyester; and other raw materials, usage amounts, and manufacturing methods are all the same as those in Comparative Example 4.
[0205] Performance test
[0206] A food preservation film was prepared by performing curtain coating on the aliphatic polyesters provided in Examples 1 to 16 and Comparative Examples 1 to 6 as follows.
[0207] Screw temperature: 145-150℃; Die temperature: 165℃; Cooling temperature: 10℃; Main machine feed speed: 27.2 kg / h; Traction roller: 11.5 Hz; Rewind roller: 11.8-13.2 Hz.
[0208] The unravelability, food contact properties, and degradation cycle of the manufactured food preservation film were tested.
[0209] The method for evaluating the unraveling index in the present invention is as follows. A completely rolled food preservation film (width 30 cm, thickness 10 ± 2 μm) is torn by about 10 cm, and the food preservation film is held with both hands and dropped from a height of 1 m. The unraveling index of the food preservation film is evaluated based on the time it takes for the food preservation film to fall to the ground. Unraveling index 1.0: free fall within 1 second; Unraveling index 1.5: free fall within 3 seconds; Unraveling index 2.0: free fall within 5 seconds; Unraveling index 2.5: free fall within 7 seconds; Unraveling index 3.0: free fall within 10 seconds; Unraveling index 4.0: free fall within 15 seconds; Unraveling index 5.0: free fall within 20 seconds. A lower unraveling index indicates superior unravelability.
[0210] In the present invention, food contactability is characterized by the amount of oligomers transferred from a food preservation film. Specifically, according to the EU10-2011 standard, under OM6 test conditions, 10% ethanol was used as a mock solution, and the amount of transfer was measured under conditions where the food preservation film thickness was 18±2 μm.
[0211] Decomposition cycle:
[0212] The above aliphatic polyester was molded into a product with dimensions of 10 cm × 10 cm and a thickness of 18 ± 2 μm, and a household composting test was performed according to the AS5810-2010 standard, and the biodegradation rate was recorded after 16 weeks of composting.
[0213] Specific test results are shown in Table 2.
[0214] [Table 2]
[0215]
[0216] As can be seen in Table 2, the aliphatic polyester of the present invention, by controlling the ratio of succinic acid and sebacic acid and controlling the oligomer content within a specific range, not only has excellent unravelability and food contact properties, but also shows a high biodegradability under household composting conditions, thereby satisfying household composting requirements.
[0217] The specific embodiments described above are intended to further explain the purpose, technical solution, and beneficial effects of the present invention. The above description is merely a specific embodiment of the present invention and should not be construed as limiting the present invention. All modifications, equivalent substitutions, improvements, etc., made in accordance with the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
Claims
Claim 1 An aliphatic polyester comprising a binary acid residue and a diol residue, wherein the binary acid residue comprises 65 to 90 mol% of a succinic acid residue based on 100 mol% of the total molar percentage content of a1) and a2); a2) comprises 10 to 35 mol% of a sebacic acid residue based on 100 mol% of the total molar percentage content of a1) and a2), and the diol residue is selected from at least equimolar amounts of 1,4-butanediol residues with respect to the binary acid residue; and wherein the aliphatic polyester comprises an oligomer having a number average molecular weight < 1000 as measured by GPC, and the mass percentage of the oligomer having a number average molecular weight < 1000 as measured by GPC in the aliphatic polyester is 0.08 to 3.45 wt%. Claim 2 In claim 1, the oligomer among the aliphatic polyesters having a number average molecular weight < 1000 as measured by GPC has the following characteristics: 0.05 wt% <q1<1.0 wt%; 0.1 wt%<q2<2.5 wt%을 갖고, q1은 GPC로 측정한 지방족 폴리에스테르 중 수평균 분자량이 500 미만인 올리고머의 질량 백분율이고; q2는 GPC로 측정한 지방족 폴리에스테르 중 수평균 분자량이 1000 미만인 올리고머의 질량 백분율이고; 바람직하게, 상기 q1은 0.1~0.6 wt%; 바람직하게, 상기 q2는 0.2~1.3 wt%인 것을 특징으로 하는 지방족 폴리에스테르. Claim 3 An aliphatic polyester according to claim 2, characterized in that the ratio of q2 to q1 is < 2, preferably the ratio of q2 to q1 is < 1.
5. Claim 4 An aliphatic polyester according to any one of claims 1 to 3, wherein the binary acid residue comprises the following residues: a1): 74 to 85 mol% of succinic acid residue based on 100 mol% of the total molar percentage content of a1) and a2); a2): 15 to 26 mol% of sebacic acid residue based on 100 mol% of the total molar percentage content of a1) and a2). Claim 5 An aliphatic polyester according to any one of claims 1 to 4, characterized in that, according to GB / T 32366-2015, the carboxyl group content of the aliphatic polyester is <40 mol / t, more preferably <30 mol / t, and even more preferably <22 mol / t. Claim 6 An aliphatic polyester characterized in that, in any one of claims 1 to 5, the intrinsic viscosity of the aliphatic polyester is 1 to 3 dL / g according to GB / T 17931-1999. Claim 7 A polyester composition, wherein the polyester composition comprises an aliphatic polyester according to any one of claims 1 to 6. Claim 8 In claim 7, the polyester composition further comprises at least one of a second polyester, a third polymer, and an auxiliary agent; preferably, the second polyester comprises at least one of polylactic acid, an aliphatic-aromatic polyester, or other aliphatic polyester; preferably, the aliphatic-aromatic polyester comprises at least one of polybutylene terephthalate, polybutylene adipate terephthalate, polybutylene sebacate terephthalate, or polybutylene adipate furandicarboxylate; preferably, the other aliphatic polyester comprises at least one of polybutylene succinate, polybutylene succinate adipate, or polybutylene sebacate; and preferably, the third polymer comprises at least one of starch, cellulose, chitin, chitosan, alginate ester, protein, gelatin, natural rubber, lignin, or a derivative of the aforementioned material. Claim 9 A packaging film, wherein the manufacturing raw material of the packaging film comprises an aliphatic polyester according to any one of claims 1 to 6, or a polyester composition according to claim 7 or 8. Claim 10 In claim 9, the unwinding index of the packaging film ≤ 3; preferably, according to the EU10-2011 standard, under OM6 test conditions, using 10% ethanol as a mock solution, and under conditions where the thickness of the packaging film is 18 ± 2 μm, the total transfer amount of the packaging film ≤ 10 mg / dm 2 Packaging film characterized by being.
